Pengembangan Bisnis Kuliner dalam Kreativitas Kewirausahaan bagi Siswa SMK di Yayasan Al Kahfi Bekasi - Enny Diah Astuti; Retno Setya Budiasningrum; Rahmi Rosita; Dyan Yuliana; Ali Satri Efendi; Jajang Setiawan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service program aims to enhance entrepreneurial competence and creativity among vocational high school (SMK) students at Yayasan Al Kahfi through a culinary business development and mentoring program. The activities focus on two key components: (1) operational business mentoring emphasizing basic food safety and production efficiency, and (2) a digital marketing workshop that trains students to create short promotional content for social media platforms. The study employs a qualitative descriptive approach through participatory observation, in-depth interviews, and documentation. The results indicate a significant improvement in students’ understanding of food safety principles, culinary product innovation, and creative digital marketing skills. Furthermore, the program encourages students to develop an adaptive entrepreneurial mindset aligned with technological and market changes in the digital era. Collaboration between lecturers, vocational teachers, and students plays a crucial role in ensuring program sustainability and integrating the outcomes into the entrepreneurship curriculum. Overall, this program contributes to nurturing a generation of vocational youth who are independent, innovative, and ready to become entrepreneurs in the digital economy.